Extracting second-order structures from single-input state-space models: application to model order reduction - Guillet, Jérôme; Mourllion, Benjamin; Birouche, Abderazik; Basset, Michel (Zielona Góra: Uniwersytet Zielonogórski)
This paper focuses on the model order reduction problem of second-order form models. The aim is to provide a reduction procedure which guarantees the preservation of the physical structural conditions of second-order form models. To solve this problem, a new approach has been developed to transform a second-order form model from a state-space realization which ensures the preservation of the structural conditions. This new approach is designed for controllable single-input state-space realizations with real matrices and has been applied to reduce a single-input second-order form model by balanced truncation and modal truncation.
Keywords: second-order form model; preservation of the structural conditions; balanced truncation; modal truncation